А П.Ковалівський - основні віхи життя та творчості - Малиновська, Н.М. (Хазарский альманах, 2005)
Professor Andry P. Kovalivsky (1895-1969) is one of the best-know Ukrainian historian and course investigator. He studied linguistic at Kharkov University. Professor Kovalivsky belongs to the Kharkiv school of comparative - history linguistics. Kovalivsky has created a original conception of Ukrainian culture history, first of all culture popular. In the center of his investigation was the phenomenon of culture popular languages, folklore, pagan belief, history and criticism of literature. He has established a firm reputation with his work about Ibn Fadlan’s papers of his journey in the Volga's Bulgarian’s tsar country (Kharkiv, 1956)